Efectivity Of Adding Hydroxypatite for Reducing Porosity on Heat Cured Acrylic Resin Base - Ronaldo Triputra Chondro; Chaterina Diyah Nanik K.; Rima Parwati Sari (Denta Journal Kedokteran Gigi, 2019)
Background: Tooth loss can be treated by using dentures. Heat cured acrylic resins are the the most common denture base materials but it has porosity that causing leftover food, plaque, bacteria, and Candida specially Candida albicans to adhere. Hydroxyapatite is chemical compound that can reduce residual monomer which causing porosity inside heat cured acrylic resin base denture. Purpose: to determine the effectivity of adding hydroxyapatite powder for reducing porosity of heat cured resins acrylic based denture. Methods: Sample were acrylic resin plate (20x10x4mm) divided into 4 groups, control group was acrylic resin without hydroxyapatite, and the treatment group was added with hydroxyapatite with concentration 2%, 5%, and 10%. After the polymerization are finished the sample was soaked on aquadest for 1 day and weighed using electronic weighing scale. The data tested with One Way ANOVA and followed by LSD test. Results: The average of porosity level on Control, treatment 1, treatment 2, treatment 3 group were 8,53%;7,75%,4,74%,5,55%. There are significant different in the porosity level between the control group and all treatment groups (p<0.05). Conclusion: Hydroxyapatite with concentration 2%, 5%, and 10% showing effectivity on reducing porosity level on heat cured acrylic resins base plate